2008
DOI: 10.1007/s00422-008-0263-8
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Hodgkin–Huxley type models for different classes of cortical and thalamic neurons

Abstract: We review here the development of Hodgkin-Huxley (HH) type models of cerebral cortex and thalamic neurons for network simulations. The intrinsic electrophysiological properties of cortical neurons were analyzed from several preparations, and we selected the four most prominent electrophysiological classes of neurons. These four classes are "fast spiking", "regular spiking", "intrinsically bursting" and "low-threshold spike" cells. For each class, we fit "minimal" HH type models to experimental data. The models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
338
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(354 citation statements)
references
References 52 publications
9
338
0
2
Order By: Relevance
“…We confirmed that the model behaves in the same way as the ionic-conductance model [11] in response to various magnitude of step input in each neuron classes.…”
Section: Introductionsupporting
confidence: 70%
“…We confirmed that the model behaves in the same way as the ionic-conductance model [11] in response to various magnitude of step input in each neuron classes.…”
Section: Introductionsupporting
confidence: 70%
“…This relationship is particularly expressed when the ISIs from the tuning curve's ascending and descending slopes are included in analyses. The role of the intrinsic biophysical properties that link ISI diversity and separation angle was demonstrated by a single-cell Hodgkin-Huxley type model (Tsanov et al, 2014a) that investigated ISI patterns ranging from irregularly-to regularly-firing type cells (Pospischil et al, 2008). These findings show that the depolarization-triggered calcium currents, together with the adaptation currents, evoke irregular firing, leading to a higher firing rate on the ascending slope of a sinusoidal depolarization (Fig.…”
mentioning
confidence: 94%
“…2(c), which is the core characteristics of RS. In this figure, it can be seen that the spike frequency converges to a higher value if the sustained stimulus is more intense, which is also a feature of RS [30]. The amount of displacement of the dynamical structure in the fast subsystem is increased and the system state converges to a limit cycle more distant from the bifurcation point.…”
Section: Rs Modementioning
confidence: 79%